Exosomes in esophageal cancer: A review on tumorigenesis, diagnosis and therapeutic potential - Su, Lin-Lin (World J Clin Cases, 2019)
Exosomes are nanovesicles secreted from various types of cells and can be isolated from various bodily fluids, such as blood and urine. The number and molecular contents, including proteins and RNA of exosomes, have been shown to reflect their parental cell origins, characteristics and biological behaviors. An increasing number of studies have demonstrated that exosomes play a role in the course of tumorigenesis, diagnosis, treatment and prognosis, although its precise functions in tumors are still unclear. Moreover, owing to a lack of a standard approach, exosomes and its contents have not yet been put into clinical practice successfully. This review aims to summarize the current knowledge on exosomes and its contents in esophageal cancer as well as the current limitations/challenges in its clinical application, which may provide a basis for an all-around understanding of the implementation of exosomes and exosomal contents in the surveillance and therapy of esophageal cancer.